Rethinking communicative interaction : new interdisciplinary horizons - Grant, Colin B. (Pragmatics & beyond, 2003)
This volume breaks open traditional disciplinary confines and approaches the full complexity of communicative interaction from an impressive range of exciting state-of-the-art perspectives in social psychology, conversation analysis, hermeneutics, constructivist psychology, communication theory, computational neuroscience, sociology of communication, second language pragmatics, ergonomic interaction theory and computer-mediated interaction studies. In so doing, it sets out to establish a new research agenda in which communication science is understood as a human-social science par excellence.